MiR-146a alleviates inflammatory bowel disease in mice through systematic regulation of multiple genetic networks - Zhu, Fengting; Yang, Taotan; Ning, Mengmeng; Liu, Yang; Xia, Wei; Fu, Yan; Wen, Ting; Zheng, Mei; Xia, Ruilong; Qian, Ran; Li, Yang; Sun, Minxuan; et al. (Frontiers in Immunology, 2024)
Introduction Inflammatory bowel disease (IBD) is a chronic disease involving multiple genes, and the current available targeted drugs for IBD only deliver moderate efficacy. Whether there is a single gene that systematically regulates IBD is not yet known. MiR-146a plays a pivotal role in repression of innate immunity, but its function in the intestinal inflammation is sort of controversy, and the genetic regulatory networks regulated by miR-146a in IBD has not been revealed. Methods RT-qPCR was employed to detect the expression of miR-146a in IBD patients and in a mouse IBD model induced by dextran sulfate sodium (DSS), and then we generated a miR-146a knock-out mouse line with C57/Bl6N background. The disease activity index was scored in DSS-treated miR-146a deficiency mice and their wild type (WT) littermates. Bulk RNA-sequencing, RT-qPCR and immunostaining were done to illustrate the downstream genetic regulatory networks of miR-146a in flamed colon. Finally, the modified miR-146a mimics were used to treat DSS-induced IBD in miR-146a knock-out and WT IBD mice. Results We showed that the expression of miR-146a in the colon was elevated in dextran sulfate sodium (DSS)-induced IBD mice and patients with IBD. DSS induced dramatic body weight loss and more significant rectal bleeding, shorter colon length, and colitis in miR-146a knock-out mice than WT mice. The miR-146a mimics alleviated DSS-induced symptoms in both miR-146a-/- and WT mice. Further RNA sequencing illustrated that the deficiency of miR-146a de-repressed majority of DSS-induced IBD-related genes that cover multiple genetic regulatory networks in IBD, and supplementation with miR-146a mimics inhibited the expression of many IBD-related genes. Quantitative RT-PCR or immunostaining confirmed that Ccl3, Saa3, Csf3, Lcn2, Serpine1, Serpine2, MMP3, MMP8, MMP10, IL1A, IL1B, IL6, CXCL2, CXCL3, S100A8, S100A9, TRAF6, P65, p-P65, and IRAK1 were regulated by miR-146a in DSS induced IBD. Among them, MMP3, MMP10, IL6, IL1B, S100A8, S100A9, SERPINE1, CSF3, and IL1A were involved in the active stage of IBD in humans. Discussion Our date demonstrated that miR-146a acts as a top regulator in C57/BL6N mice to systematically repress multiple genetic regulatory networks involved in immune response of intestine to environment factors, and combinatory treatment with miR-146a-5p and miR-146a-3p mimics attenuates DSS-induced IBD in mice through down-regulating multiple genetic regulatory networks which were increased in colon tissue from IBD patients. Our findings suggests that miR-146a is a top inhibitor of IBD, and that miR-146a-5p and miR-146a-3p mimics might be potential drug for IBD.